Digital Green Economy Module to Foster Green Behavior in Grade X Students - Ainiyah, Maf Ulatul; Subroto, Waspodo Tjipto; Hakim, Luqman (Sumber Belajar Sejahtera, 2025)
Global environmental crises, driven by unsustainable economic practices, highlight the urgent need for a transition toward a green economy. Education plays a crucial role in this transition by fostering green behavior among the younger generation. However, a significant gap exists in the availability of specific teaching materials that integrate green economy concepts into the economics curriculum within a local context. This study addresses that gap by developing and testing a digital-based Green Economy Module for 10th-grade students in an environmentally vulnerable region. Employing a Research and Development (R&D) approach using the ADDIE model, this study created a learning module that underwent rigorous validation by content, language, and graphics experts, achieving a